FRI0288 Nailfold capillaroscopic pictures in a cohort of undifferentiated connective tissue disease (UCTD) patients and in those that move to systemic lupus erythematosus. (15th June 2017) - Meroni, M; Pizzorni, C; Sulli, A; Limonta, M; Cutolo, M
Abstract : Background: Nailfold capillaroscopy (NVC) is a useful, non-invasive, reproducible and cost-effective diagnostic tool, able to assess the shape of capillaries in the nailfold bed. According to the presence of peculiar abnormalities, it is essential in the early differential diagnosis of connective tissue diseases (CTDs), mainly "scleroderma-spectrum disorders" (SSD). Despite its large diffusion, no univocal NVC patterns have been ascribed to undifferentiated connective tissue disease (UCTD) as well as to systemic lupus erythematosus (SLE). Objectives: The aim of the study was to evaluate the most common NVC pictures in a population of UCTD patients and if selected NVC pictures might be linked to SLE onset in these patients. Methods: We evaluated a cohort of 42 UCTD-affected women, diagnosed according to 2014 criteria proposed by Mosca et al. (age, 38 years±46 months; duration of disease, 71±54 months) presenting Raynaud's phenomenon. During the observational period (3 years), all of the UCTD patients were evaluated every 6 months. We considered the following NVC parameters/pictures: presence of ectasic capillary loops (diameter ≥20 μm); giant capillaries (diameter ≥50 μm); hemosiderin deposits/microhemorrages; capillary number reduction; meandering capillaries (tortuosity); elongated capillaries; ramified/bushy capillaries; micro-vascular array disorganization. SLE diagnosis was posed according to the 2012 SLICC/ACR criteria. Qualitative variables were expressed in frequencies; their association, by non-parametric tests; quantitative variables, by analysis of co-variance. Results: Non-specific NVC alterations (for instance, not suggestive of SDD) were detected in 40 (98%) of the UCTD patients during the observational period. On the other hands, the presence of hemosiderin deposits, ectasic loops, elongated and ramified capillaries was found associated to the clinical subgroup of UCTD patients that later developed SLE (4/42 subjects, 10%; OR=10.5). In particular, the independent variables "hemosiderin deposits/microhemorrages" (OR=8.32) and "elongated capillaries" (OR 6.28), were found significantly linked to the SLE onset (p<0.05), whereas the independent variables "tortuosity" (OR=12.16) and "ramified/bushy capillaries" (OR 9.47) were, at the opposite, predictive for the prosecution of the status of UCTD patient (p<0.05). Conclusions: The present study reports NVC pictures that can be more frequently observed in UCTD patients that include "tortuosity" and "ramified/bushy capillaries". In addition, the NVC analysis suggests the presence of typical capillaroscopic microvascular abnormalities, "hemosiderin deposits/microhemorrages" and "elongated capillaries", that more frequently seem observed in those UCTD patients that move to SLE onset. References: Hughes M et al. Best Pract Res Clin Rheumatol. 2016;30:112–32. Ingegnoli F, et al. J Clin Rheumatol. 2005;11(6):295–8. Mosca M, et al. J Autoimmun. 2014;48–9:50–2. Cutolo M et al. Best Pract Res Clin Rheumatol. 2005;19(3):437–52. Disclosure of Interest: None declared